Enhanced boron transport into the ear of wheat as a mechanism for boron efficiency - Nachiangmai D. (2014)
Genotypic variation in boron (B) efficiency in wheat (Triticum aestivum L.) is expressed as large differences in grain set and pollen fertility under low soil B, but the mechanisms responsible for such differences are unknown. This paper aims to determine whether differences in B transport and retranslocation can explain cultivar differences in B efficiency between B-efficient (Fang 60) and B-inefficient (SW41) wheat cultivars. Plants were grown with adequate 11B (10 μM), until the premeiotic interphase stage in anther development, then transferred into 10B at 0.1 or 10 μM. After five days, ending at the young microspore stage, plants were returned to adequate 11B. Plants were harvested at 0, 1 and 5 days after transferring into 10B, and at anthesis when fresh pollen was examined for viability. After 5 days in 0.1 μM B, pollen viability in SW41 was depressed by 47%, but pollen of Fang 60 was not affected. When B supply was low, the proportion of plant B partitioned into the ear of Fang 60 was almost twice as high as that in SW 41, enabling Fang 60 to maintain B concentration in the ear at 6.8 mg kg -1 dry weight (DW), whereas it dropped to 3.8 mg kg-1 DW in SW 41. Boron accumulation in the ear, when external supply was restricted, did not come from the 11B previously taken up by the plant. The greater 10B accumulation in ears of Fang 60 compared to SW 41, with limited external B supply, indicated that B efficiency was associated with xylem transport of B. The greater increase of 10B:11B ratio in the ear of Fang 60 compared to SW 41, over the 5 days of B interruption further indicated that greater B efficiency was associated with a stronger capability for long distance transport of B from the rooting medium into the ear via the xylem rather with than retranslocation of B from vegetative parts. © 2004 Kluwer Academic Publishers.